Advances in understanding molecular mechanisms of fungicide resistance and molecular detection of resistant genotypes in phytopathogenic fungi - Zhonghua Ma; Themis J. Michailides
Although fungicide treatments are a key component in the integrated management of many plant diseases, the appearance of resistance has become an important factor in limiting the efficacy and useful lifetime of fungicides developed at increasingly higher costs. Extensive molecular studies have led to advances in our understanding of mechanisms of fungicide resistance and in developing effective, rapid methods for detection of resistant genotypes of pathogens. This paper reviews recent advances in our understanding of resistance mechanisms of phytopathogenic fungi to some major classes of fungicides (benzimidazoles, demethylation inhibitors [DMIs], Qo respiration inhibitors [QoIs], and dicarboximides [DCFs]) at a molecular level and developments in molecular detection of fungicide-resistant fungi.
Keywords: BENZIMIDAZOLES; DEMETHYLATION INHIBITORS (DMIS); DICARBOXIMIDES; FUNGICIDE RESISTANCE; QO RESPIRATION INHIBITORS (QOIS); STROBILURINS